1963
DOI: 10.1271/bbb1961.27.663
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of the Major Anthocyanin in Eggplant

Abstract: The Structure of the Major Anthocyanin in Eggplant Sir: Kuroda and Wadan isolated a major anthocyanin in eggplant, nasunin, and proposed. its structure as delphinidin-3-diglucoside acylated with p-coumaric acid. They also re

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

1966
1966
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…Interestingly, the major anthocyanins detected in this study in tomato, namely nasunin and petanin, have both been identified previously in other Solanaceous species. Nasunin (also named violanin) is particularly well characterized eggplant (S. melongena; Kuroda and Wada, ; Sakamura et al ., ), as well as potato (Goto et al ., 1978), pepper (Sadilova et al ., ) and petunia (Schram et al ., ) although it is also present in Iris tingitana (Harborne, ; Nerdal and Andersen, ) and Viola tricolor (Harborne and Baxter, ), whereas petanin is particularly well characterized in petunia (Schram et al ., ), as has been described in potato, Solanum nigrum and Iris (Harborne and Baxter, ). Other anthocyanin derivatives exhibiting 3– O ‐(4′′′–phenylacyl‐rutinoside)‐5– O ‐glucoside decorations have mostly been described in Solanaceous species (petunia species, eggplant, potato and S. nigrum ), but also with additional species of iris, Ipomoea indivisia and Silene dioica (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the major anthocyanins detected in this study in tomato, namely nasunin and petanin, have both been identified previously in other Solanaceous species. Nasunin (also named violanin) is particularly well characterized eggplant (S. melongena; Kuroda and Wada, ; Sakamura et al ., ), as well as potato (Goto et al ., 1978), pepper (Sadilova et al ., ) and petunia (Schram et al ., ) although it is also present in Iris tingitana (Harborne, ; Nerdal and Andersen, ) and Viola tricolor (Harborne and Baxter, ), whereas petanin is particularly well characterized in petunia (Schram et al ., ), as has been described in potato, Solanum nigrum and Iris (Harborne and Baxter, ). Other anthocyanin derivatives exhibiting 3– O ‐(4′′′–phenylacyl‐rutinoside)‐5– O ‐glucoside decorations have mostly been described in Solanaceous species (petunia species, eggplant, potato and S. nigrum ), but also with additional species of iris, Ipomoea indivisia and Silene dioica (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…We identified considerable alterations in a total of 113 compounds, which included seven anthocyanins and 18 flavonol derivatives. We characterized the major anthocyanins as delphinidin‐3– O‐ [4′′–( trans‐p– coumaroyl)‐α– l ‐rhamnopyranosyl‐(1→6)‐β– d ‐glucopyranoside]‐5– O ‐β– d ‐glucopyranoside (TA1, commonly referred to as nasunin and violanin) and petunidin‐3– O ‐[4′′′–( trans‐p– coumaroyl)‐α– l ‐rhamnopyranosyl‐(1→6)‐β– d ‐glucopyranoside]‐5– O ‐β– d ‐glucopyranoside (TA2, petanin), which have already been characterized in aubergine/eggplant (Kuroda and Wada, ; Sakamura et al ., ) ( Solanum melongena ) and petunia (Schram et al ., ), respectively. Integration of metabolomic and transcriptomic data allowed us to speculate about the genetic and biochemical mechanisms underlying the alterations in these profiles.…”
Section: Introductionmentioning
confidence: 99%
“…The major antioxidant components of onion and eggplant are 2 types of quercetin glycosides (Tsushida & Suzuki, 1995;Price et al, 1997) and nasunin (Sakamura et al, 1963), respectively. Broccoli contains quercetin glycosides, kaempferol glycosides and 4 types of hydroxycinnamic acid esters as the major antioxidant components (Plumb et al, 1997;Price et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Nasunin is the one isolated from eggplant (20). It is generally accepted that acylated anthocyanins are relatively more stable than nonacylated anthocyanins (23), and some acylated anthocyanins have been reported to have unique physiological functions (24,25).…”
Section: Introductionmentioning
confidence: 99%